2008
DOI: 10.1007/s11224-008-9309-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, IR spectrum, thermal property and crystal structure of cyano-bridged heteronuclear polymeric complex, [Cd(teta)Ni(μ-CN)2(CN)2] · 2H2O

Abstract: The cyano-bridged heteronuclear polymeric complex, [Cd(teta)Ni(l-CN) 2 (CN) 2 ] Á 2H 2 O (1), (teta = triethylenetetraamine) was synthesized and characterized by FT-IR spectroscopy, thermal analysis and single crystal X-ray diffraction techniques. It crystallizes in the orthorhombic system, space group Pccn. The asymmetric unit also contains two uncoordinated water molecules. The coordination geometry around the Cd(II) centre is a highly distorted octahedral. In the crystal structure, intramolecular N-HÁÁÁO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…ion is squareplanar and the Ni-C bond distances of 1.860(3) and 1.870(3) Å are expectedly shorter than in [Cu(hydeten) 2 Pd(CN) 4 ] [20] and [Cu(hydeten) 2 Pt(CN) 4 ] [29] because of the difference of ion radii [32]. In contrast, the Ni-C bond lengths of [Zn(hydeten) 2 Ni(CN) 4 ] [23] and [Cd(teta) 2 Ni(l-CN) 2 Ni(CN) 2 ]Á2H 2 O (teta = triethylenetetraamine) [33] are roughly similar to those in c2. In addition, the bond angles of C5-Ni-C5 b and C6-Ni-C6 b (Table 2) are completely linear, as the bond angles of C5-Ni-C6 are almost 90°.…”
Section: Resultsmentioning
confidence: 99%
“…ion is squareplanar and the Ni-C bond distances of 1.860(3) and 1.870(3) Å are expectedly shorter than in [Cu(hydeten) 2 Pd(CN) 4 ] [20] and [Cu(hydeten) 2 Pt(CN) 4 ] [29] because of the difference of ion radii [32]. In contrast, the Ni-C bond lengths of [Zn(hydeten) 2 Ni(CN) 4 ] [23] and [Cd(teta) 2 Ni(l-CN) 2 Ni(CN) 2 ]Á2H 2 O (teta = triethylenetetraamine) [33] are roughly similar to those in c2. In addition, the bond angles of C5-Ni-C5 b and C6-Ni-C6 b (Table 2) are completely linear, as the bond angles of C5-Ni-C6 are almost 90°.…”
Section: Resultsmentioning
confidence: 99%
“…The shift to lower frequencies of (OH) stretching modes and the shift to higher frequencies of (OH) bending modes (1620-1650 cm -1 ) may be attributed to hydrogen bonding in the complexes. In our previous study [19], the available of water molecules in the structures of the complexes were identified by the vibrational analysis and was supported by X-ray diffraction. Pyridazine vibrations.…”
Section: Vibrational Spectramentioning
confidence: 94%
“…Hofmann-type complexes are formulated as [M(L) 2 Ni(CN) 4 ] n , where M is a transition metal such as Co(II), Ni(II), Cu(II) or Cd(II), and L is an amine ligand such as ammonia [14], ethylenediamine [7-9, 19, 22], diethylenetriamine [10,21], triethylenetetramine [26] or pyridine [21]. In these complexes, Ni(II) is in a square-planar environment with the C atoms of four CN ligands, and M exhibits octahedral geometry with two L and N atoms of four CN ligands and, therefore, Hofmann-type complexes have a three-dimensional polymeric host structure for inclusion of small guest molecules such as benzene, thiophene and aniline [4,27].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous [26], we reported the infrared spectrum, thermal property, and crystal structure results of cyanobridged heteronuclear polymeric complex, [Cd(teta)Ni (l-CN) 2 however, to the best our knowledge, neither crystallographic, nor spectroscopic data have been so far would explicitly tell the structural analyses of the 2mpz-metal(II) complexes of tetracyanonickelate(II) ions.…”
Section: Introductionmentioning
confidence: 99%